The Effect of Perpendicular Lamp Position on Normal Plane Alignment for Light Distribution and Coverage in Adaptive Headlamps During Complex Driving Scenarios - Ian Hardianto Siahaan; I Nyoman Sutantra; I Made Londen Batan (Automotive Experiences, 2025)
Due to decreased visibility and an increased chance of accidents, driving at night requires increased vigilance. Drivers must be equipped to handle various road and terrain conditions, such as declines, inclines, turns, straight paths, and combinations. Following the law and ethical driving standards is crucial in these circumstances. Inadequate street illumination, poor lighting, and inexperienced drivers are all common causes of accidents. The risks increase at night when little ambient lighting reduces visibility. This study investigates the distribution of light intensity and illumination radius via a factorial design derived from headlamp activation configuration scenarios, simulated in MATLAB software, and validated using experimental test results. The results show that driver focus and vision range improve dramatically, particularly when the lights are triggered on flat roads, during turns, climbs, and combinations of these actions, by the New ADHL's headlamp activation configuration. Simulation-based activation of main and auxiliary light configurations shows that the New ADHL outperforms traditional headlamps, effectively addressing insufficient illumination to prevent nighttime accidents and providing a coverage radius of more than 3.5 m at the lowest intensity detectable by the driver.